Tax System Design, Tax Reform, and Labor Supply - Katharina Pfeil; Matthias Kasper; Sarah Necker; Lars P. Feld (CESifo GmbH, 2024)
This study examines how tax system design and reform affect labor supply. We conduct an online experiment with 522 participants to assess labor responses to tax reforms that introduce or remove a notch, affecting after-tax income at either the lower or upper end of the income distribution. Our findings indicate asymmetric responses to tax reform as well as substantial heterogeneity at the individual level. In particular, we find an increase in labor supply in response to a tax reform only when the reform reduces the tax burden at the upper end of the income distribution. While, in the aggregate, labor supply adjusts on the extensive and intensive margins, we also find strong evidence of heterogeneity in individual responses, showing that the labor response is primarily driven by individuals directly affected by the reform. We examine the role of misperceptions at the individual level as well as fairness considerations in explaining these results.
Keywords: J20; J22; H24; H30; C91; 330; tax system design; tax reform; notches; labor supply; online experiment